Differences in receptor-evoked membrane electrical responses in native and mRNA-injected Xenopus oocytes. - Oron, Y (1988)
Xenopus laevis oocytes are giant cells suitable for studies of plasma membrane receptors and signal transduction pathways because of their capacity to express receptors after injection of heterologous mRNA. We studied depolarizing chloride currents evoked by acetylcholine (AcCho) in native oocytes ("intrinsic AcCho response"), by thyrotropin-releasing hormone (TRH) in oocytes injected with pituitary (GH3) cell RNA ("acquired TRH response"), and by AcCho in oocytes injected with rat brain RNA ("acquired AcCho response"). We found differences in the latencies and patterns of these responses and in the responsiveness to these agonists when applied to the animal or vegetal hemisphere, even though all of the responses are mediated by the same signal transduction pathway. The common intrinsic response to AcCho is characterized by minimal latency (0.86 +/- 0.05 sec), a rapid, transient depolarization followed by a distinct prolonged depolarization, and larger responses obtained after AcCho application at the vegetal rather than the animal hemisphere. By contrast, the acquired responses to TRH and AcCho are characterized by much longer latencies, 9.3 +/- 1.0 and 5.5 +/- 0.8 sec, respectively, and large rapid depolarizations followed by less distinct prolonged depolarizations. The responsiveness on the two hemispheres to TRH and AcCho in mRNA-injected oocytes is opposite to that for the common intrinsic AcCho response in that there is a much greater response when agonist is applied at the animal rather than the vegetal hemisphere. We suggest that the differences in these responses are caused by differences in the intrinsic properties of these receptors. Because different receptors appear to be segregated in the same oocyte in distinct localizations, Xenopus oocytes may be an important model system in which to study receptor sorting in polarized cells.